Chaos based image encryption security in cloud computing. (19th May 2022) - Kumar, Sarvesh; Srivastava, Prabhat Kumar; Srivastava, Gaurav Kumar; Singhal, Prateek; Singh, Dinesh; Goyal, Dinesh
Abstract: In the rapid world of technology, the IT Industry is growing at a rapid speed with Cloud Image Security. In the developing trends, cloud orchestration is becoming impressive and uncertain of dealing a large amount of information. In the last two decades there has been extensive development in image encryption. Chaos based image encryption techniques form framework for a faster algorithm than traditional techniques. Chaos based techniques are highly efficient in case of multimedia data. The proposed algorithm uses the modified logistic map for the generation of chaotic sequence, encrypts the image in single scan, so runs faster and makes the proper use of confusion and diffusion. It dynamically updates the key during execution. This algorithm is secure against the brute force attack and differential attack.